Bio-Waste from Urban and Rural Areas as a Source of Biogas and Methane—A Case Study from Poland - Wojciech Dronia; Jakub Kostecki; Jacek Połomka; Andrzej Jędrczak (Energies, 2024)
The growing volume of household waste, especially bio-waste, poses a significant challenge to waste management systems. In Poland, bio-waste accounts for almost one third of total waste generation. To address this challenge, in the context of optimising the waste biomass value chain, we are investigating the potential of methane fermentation to convert bio-waste into valuable end products in the form of digestate (organic recycling) and biogas (a renewable energy source with a wide range of downstream applications). This paper presents the moisture content, loss on ignition and biogas and methane production efficiency for bio-waste and for the seven types of waste that are the main constituents of selectively collected bio-waste (meat, other edible waste (dairy), fruits and vegetables, grass, leaves, branches and the < 10 mm fraction). Data on the technological properties of bio-waste and its constituents may be of interest to a range of stakeholders. The average moisture content ranged from 41.9% (<10 mm fraction and others) to 84.4% (fruits and vegetables), and the average organic matter content of the dry weight of the waste ranged from 37.8% (<10 mm fraction and others) to 88.7% (edible constituents other than meat and fruits and vegetables). The bio-waste had an average moisture content of 71.3 ± 1.7% and loss on ignition of 68.6 ± 1.7%. Biogas production from selectively collected bio-waste ranged from 285 to 404 Ndm3∙kg−1 DM (mean: 347 ± 53 Ndm3∙kg−1 DM), and methane production ranged from 191 to 271 Ndm3∙kg−1 DM (mean: 215 ± 33 Ndm3∙kg−1 DM).